Managing the Bots That Are Managing the Business - O'Reilly, Tim; Davenport, Thomas (MIT Sloan Management Review, 2016)
We are just at the beginning of the transformation from an economy dominated by human workers to one dominated by electronic workers. The great management challenge of the next few decades will be understanding how to get the best out of both humans and machines, and understanding the ins and outs of who manages whom.